WSV181 inhibits JAK/STAT signaling and promotes viral replication in Drosophila. (March 2019) - Wang, Wei; Pan, Changkun; Huang, Zongliang; Yuan, Huifang; Chen, Jianming
Abstract: The Janus kinase/signal transducers and activators of transcription (JAK/STAT) pathway plays a critical role in host defense against viral infections. Here, we report the use of the Drosophila model system to investigate the modulation of the JAK/STAT pathway by the white spot syndrome virus (WSSV) protein WSV181. WSV181 overexpression in transgenic flies resulted in the downregulation of STAT92E and STAT92E-targeted genes. This result indicates that WSV181 can suppress JAK/STAT signaling by controlling STAT92E expression. An infection experiment was carried out on transgenic Drosophila infected with Drosophila C virus and on Litopenaeus vannamei injected with recombinant WSV181 and WSSV. The increased viral load and suppressed transcript levels of JAK/STAT pathway components indicate that WSV181 can promote viral proliferation by inhibiting the JAK/STAT pathway. This study provided evidence for the role of WSV181 in viral replication and revealed a new mechanism through which WSSV evades host immunity to maintain persistent infection. Highlights: JAK/STAT pathway is inhibited in flies with ectopic WSV181 expression. WSV181 reduces the expression but does not alter phosphorylation level of STAT92E. WSV181 promotes viral load and repressed JAK/STAT pathway during viral infection. WSV181 expression impaires resistance against viral infection.